Concurrent Genetic Alterations and Other Biomarkers Predict Treatment Efficacy of EGFR-TKIs in EGFR-Mutant Non-Small Cell Lung Cancer: A Review - Guo, Yijia; Song, Jun; Wang, Yanru; Huang, Letian; Sun, Li; Zhao, Jianzhu; Zhang, Shuling; Jing, Wei; Ma, Jietao; Han, Chengbo (Frontiers in Oncology, 2020)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) greatly improve the survival and quality of life of non-small cell lung cancer (NSCLC) patients with EGFR mutations. However, many patients exhibit de novo or primary/early resistance. In addition, patients who initially respond to EGFR-TKIs exhibit marked diversity in clinical outcomes. With the development of comprehensive genomic profiling, various mutations and concurrent (i.e., coexisting) genetic alterations have been discovered. Many studies have revealed that concurrent genetic alterations play an important role in the response and resistance of EGFR-mutant NSCLC to EGFR-TKIs. To optimize clinical outcomes, a better understanding of specific concurrent gene alterations and their impact on EGFR-TKI treatment efficacy is necessary. Further exploration of other biomarkers that can predict EGFR-TKI efficacy will help clinicians identify patients who may not respond to TKIs and allow them to choose appropriate treatment strategies. Here, we review the literature on specific gene alterations that coexist with EGFR mutations, including common alterations (intra-EGFR [on target] co-mutation, TP53, PIK3CA, and PTEN) and driver gene alterations (ALK, KRAS, ROS1, and MET). We also summarize data for other biomarkers (e.g., PD-L1 expression and BIM polymorphisms) associated with EGFR-TKI efficacy.